A Study to Assess the Challenges Faced and Measures Taken by the Mothers of Children with Attention-Deficit Hyperactivity Disorder in a Selected Hospital, Kolkata, West Bengal - Soumi Mandal; Bhanumati Dutta (Indian Journal of Psychiatric Nursing)
Context: Children with attention-deficit hyperactivity disorder (ADHD) present a big challenge to mothers. They experience burden and lack of support and resources in child's care. Aims: This study aimed to assess the challenges faced and measures taken by mothers of children with ADHD. Settings: The present study was conducted at Outpatient Department of Manovikas Kendra, 482, Madudah. Plot 1-24, Sector - J, E. M. Bypass, Kolkata-700 107, West Bengal. Design: This was a descriptive survey approach. Subjects and Methods: Data were collected from 86 mothers included by nonprobability convenience sampling technique. Rating scale and semi-structured interview schedule were used to collect data. Statistical Analysis Used: Descriptive and inferential statistics was used for statistical analysis. Results: The findings revealed that only 2 (2.32%) mothers of children with ADHD faced mild (0–25), 81 (94.18%) mothers of children with ADHD faced moderate level (26–51), 3 (3.48%) mothers of children with ADHD faced severe (52–76) level of challenges, and all mothers (100%) used punishment/beating, provided the child toys for calming down, kept child under supervision, and praised their willingness to study rather than getting full marks. The computed Chi-square result showed significant association between level of challenges faced by the mothers with types of family, education qualification, and monthly family income (p < 0.05). Conclusions: Majority (94.18%) of the mothers of children with ADHD faced moderate level of challenges.